The effects of back and forth jump training with vascular occlusion in college male judo player - Ohkawa, Y.; Ozawa, Y.; Ishibashi, G. (Association for the Scientific Studies on Judo, Kodokan, 2017)
The purpose of this paper is to investigate the effects of back and forth jump training with vascular occlusion. Body composition, such as weight, skelet.al muscle mass and muscle mass of arms and legs is measured and the number of repetitions of the jump is counted before and after the jump training sessions in order to evaluate the effects of them.